Production Performance of Broilers Fed with Aloe vera and Curcuma longa (Turmeric) - Mehala, C.; Moorthy, M. (International Journal of Poultry Science, 2008)
An experiment was conducted to study the inclusion of Aloe vera and Curcuma longa and its combinations on production performance, viz., weight gain, feed intake and feed conversion ratio, carcass characteristics and biochemical parameters for a period of six weeks with two hundred and eighty commercial, straight run day-old Vencobb broiler chicks. These chicks were randomly grouped into seven treatments with four replicates of ten chicks each. The treatment groups consisted of control (T1), 0.1 percent Aloe vera powder (T2), 0. 2 percent Aloe vera powder (T3), 0.1 percent Curcuma longa powder (T4), 0.2 percent Curcuma longa powder (T5) and 0.1 percent of Aloe vera and 0.1 percent of Curcuma longa powder (T6) and 0.2 percent of Aloe vera and 0.2 percent of Curcuma longa powder (T7) included in the broiler diet. The results revealed that there was no significant difference in body weight and body weight gain between treatment groups from first week to end of the experiment period except at first week (P < 0.01). Similarly, no significant difference was recorded in feed consumption and carcass yields, but in feed conversion ratio significant (P < 0.01) difference was recorded at first week of age. Livability was 100 percent in T2 and T3 treatment groups. The mean return over feed cost differs significantly (P < 0.01) between treatment groups up to six weeks of age, which was mainly due to difference in feed cost of Aloe vera and Curcuma longa inclusion in broiler diet.